REMAJA, KEKERASAN, DAN PENDIDIKAN KELUARGA: FENOMENA KLITIH DI YOGYAKARTA - Isnaini Lubis; Zulkipli Lessy; Ahmad Lailatus Sibyan (The Institute for Research and Community Service (LP2M) of Pontianak State Institute of Islamic Studies (IAIN Pontianak), 2023)
Klitih is a juvenile delinquent in the Special Region of Yogyakarta and is a social violence committed by young people due to many reasons, such as lack of parental care and the failure of schools in fostering positive character. Klitih is a type of youth anarchism carried out on the street by teenagers using samurai, swords, and knives to randomly stab people at night time. This study aims to determine how effective is the parenting role in addressing klitih among adolescents in Yogyakarta. Type of the study is field research with subjects that consist of five parents and five teachers in Banguntapan District, Bantul Regency, Special Region of Yogyakarta, and relevant documents of the literature study. The research is a descriptive analysis where the researchers used interview narratives and citations of journals and books as either primary or secondary sources. The results show that parenting in dealing with adolescent clients focuses on three aspects: first, warmth which is determined by parents’ affection and emotional involvement with their children. Second, control which is characterized by parents who enforce discipline on their children. Third, communication between parents and children should maintain open communication. Furthermore, the roles of educational institutions in addressing klitih among teenagers are: the existence of moral education, value education, religious education, social education, intellectual education, spiritual education, democratic education, and the existence of extracurricular activities to instill character education in children.